Gestión de inventarios y su incidencia en la rentabilidad financiera de la empresa ferrehierro del cantón Quevedo, año 2022. - Ramos Guevara, Liseth Carolina (2024)
In the research carried out, the objective was to evaluate inventory management and its impact on the financial profitability of the company FerreHierro, which is dedicated to the sale of hardware items and manufactures in the city of Quevedo, with the purpose of identifying the shortcomings that have been presented in this area and establish policies and procedures for more efficient management compared to what they have been carrying out. In this research, analytical and inductive methods were used, the research design was descriptive, correlational and documentary, according to the objectives set for obtaining information, field techniques were also used such as direct observation, documentary analysis, surveys and interviews, which were applied to all workers and managers, which is the study population. The results obtained through the analysis of the surveys and interviews allowed us to identify the current situation and inventory management model they use, which is an important activity in the hardware store and with this flow of real information, the critical points that affect the financial profitability, which was determined with the analysis of the financial statements and application of indicators, given the above, a manual of inventory policies and procedures was established with suggestions for technological tools and information systems most suitable for correct management of inventories at FerreHierro.